Two new species and new records of Quedius from Nepal (Coleoptera: Staphylinidae: Staphylininae). - Solodovnikov, Alexey Yurievich; Kleeberg, Andreas (Contributions to Entomology = Beiträge zur Entomologie, 2004)
Two new species of Quedius are described from Nepal: Quedius (Microsaurus) lamjung sp. n. and Quedius (Raphirus) tingra sp. n. Syntype of Quedius (Raphirus) aureiventris Bernhauer is examined and the non-type based identification of this species in the revision of Smetana (1998) is proved to be correct. In addition to two new species, new records are provided for eleven species of Quedius distributed in Nepal Himalayas. Keywords Quedius, new species, syntype, new records, Nepal, Himalayas. Nomenclatural Acts tingra Solodovnikov & Kleeberg, 2004 (Quedius), spec. n. lamjung Solodovnikov & Kleeberg, 2004 (Quedius (Microsaurus)), spec. n.